La destruction des villages de pêcheurs au sud de Libreville. Une opération entre impératif sécuritaire et spéculation foncière - Serge Loungou (L'Espace Politique)
The demolition, in 2002, of West-African fishermen’s villages established in the municipality of Owendo, South of Libreville, capital of Gabon, had officially been justified by the necessity to fight against illegal immigration by sea and criminality forms which are associated with it. The author of this article tries to bring another explanation to this decision, which is partially linked to a vast land speculation operation orchestrated by the Gabonese Port and Harbor Office (OPRAG), to economically promote the immense state-owned ground which it possesses in the municipality.